An investigation into high precision control of the relative angular position of two shafts over a range of speeds and ratios - Healey, M. (College of Aeronautics, 1964)
SUMMARY The paper sets out to describe how a servo mechanism may be applied to generative gear grinding machines and an appropriate specification is drawn up. The system involves separate motor drives to the two shafts, the angular positions of which are monitored with radial diffraction gratings. One of the signals is frequency divided to achieve the speed ratio between the two shafts, the resultant similar frequency signals being phase compared, any difference producing an error signal thus completing the servo loop. Hydraulic motors are used as prime movers. The transfer functions of the loop are developed and compared with measured open loop results. It is clearly shown that with the components at present available the loop cannot be made stable. The specification of more appropriate hardware is discussed and future work outlined, but the conclusion is reached that this system cannot be used for its primary purpose on a generative gear grinding machine.